Maternal and Perinatal Outcomes in Placenta Previa - Saba Jassim Al Hashimi; Aqeela Haider Majeed; Ahmed Majed Shayal ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
Background: detection of the Sociodemographic pattern and maternal, perinatal outcomes of pregnant mothers with placenta previa. Setting: This prospective research done at government General Hospital (Al-Sadder Teaching Hospital), Misan, Iraq during the period of October 2016 to April 2017. Patients & methods: all Women who complaint of painless vaginal bleeding or those diagnosed as having placenta previa on routine ultrasound examination after 28 weeks of gestational age were included in this research and were evaluated with demographic profile, comprehensive maternal history, clinical examination, laboratory investigation, type of placenta previa on ultrasound examination, impact of previous mode of delivery and present mode of delivery, maternal and perinatal complications, the incidence of primary postpartum hemorrhage and the need for transfusion of blood were noted. Results: Incidence of Placenta previa was 0.6% (40/6512). Mean age of presentation was 31yrs. Multigravida (90%), (82.5%) presented between 28-36+6 weeks gestational age and (17.5%) presented between 37 - 42 weeks, Antepartum hemorrhage (62.5%), malpresentation (20%), women with previous history of surgical intervention (55%), (25%) with previous cesarean delivery, (12.5%) with dilatation and Curettage for abortion, and (17.5%) with both. (22.2%) had Postpartum hemorrhage, (42.5%) needed blood transfusion, (2.5%) abdominal hysterectomy was done, Neonatal intensive care unit admission (30.5%) because of (jaundice, preterm baby, dyspnea and cyanosis, hydrops Fetalis), maternal mortality was nil and neonatal mortality was (5.5%). Conclusion: The presence of placenta previa carries a great danger to the mother & her baby with a high risk of adverse maternal & perinatal outcomes if not treated in the proper time .